Peningkatan Kemampuan Dan Kesiapsiagaan Siswa Sekolah Terhadap Mitigasi Bencana Di Jorong Padang Panjang Kecamatan Pariangan Kabupaten Tanah Datar - Silvia Santi Yutaro; Rahmadani Yusran; Thaufik Qurrhahim Rinaldi; Zikri Illahi (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Nagari Pariangan is located at the foot of Mount Marapi and has several potential disasters such as volcanic eruptions, volcanic earthquakes and landslides. The research method used is qualitative research - descriptive which aims to describe, explore, or understand phenomena in depth and detail. Disaster mitigation training carried out through outreach, delivery of material on disaster mitigation, preparing evacuation routes and gathering points. Dissemination of disaster mitigation aims to increase awareness, knowledge, and community preparedness in dealing with disasters and this can be said to be successful. Disaster mitigation training with outreach, delivery of materials, and preparation of evacuation routes and assembly points is an important step in increasing community preparedness and safety in facing disasters. Seeing how disaster mitigation training activities carried out through outreach, delivering materials and preparing evacuation routes and gathering points were carried out successfully, it is hoped that a generation that is more aware, ready to face challenges, and able to contribute in protecting themselves and others in the face of disasters is formed.